2014
DOI: 10.1075/ts.3.03orr
|View full text |Cite
|
Sign up to set email alerts
|

Subtitling, video consumption and viewers

Abstract: The emergence of international audiences and the activities of prosumers are modifying international media flows. Consumers have become active mediators in the distribution of audiovisual contents through the Internet, overstepping official distribution channels. As an efficient way to overcome linguistic barriers, non-professional subtitling plays an important role within this framework. In order to analyze how the new environment is altering users' behavior and attitudes, this article looks at the case of vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
4
1

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(8 citation statements)
references
References 4 publications
0
8
0
Order By: Relevance
“…To approach the reception side and as an attempt to assess how people feel about nonprofessional subtitling, whether they use them and what the impact of these subtitles is, I carried out an experiment to study the reception of non-professional subtitles at the Universitat Rovira i Virgili in 2013 (Orrego-Carmona 2014, 2016a, and collected and analyzed Internet data (Orrego-Carmona 2014; Orrego-Carmona and Richter 2018). To operationalize reception, I relied on Gambier's proposal to study reception at three levels: "reactions on the cognitive level, responses in behavioural terms and repercussions of a cultural order" (Gambier 2008, emphasis in the original).…”
Section: The Reception Conditionsmentioning
confidence: 99%
See 1 more Smart Citation
“…To approach the reception side and as an attempt to assess how people feel about nonprofessional subtitling, whether they use them and what the impact of these subtitles is, I carried out an experiment to study the reception of non-professional subtitles at the Universitat Rovira i Virgili in 2013 (Orrego-Carmona 2014, 2016a, and collected and analyzed Internet data (Orrego-Carmona 2014; Orrego-Carmona and Richter 2018). To operationalize reception, I relied on Gambier's proposal to study reception at three levels: "reactions on the cognitive level, responses in behavioural terms and repercussions of a cultural order" (Gambier 2008, emphasis in the original).…”
Section: The Reception Conditionsmentioning
confidence: 99%
“…Twitter data on the broadcasting of a subtitled version of Game of Thrones on Canal+ Spain in 2014 revealed that for some viewers, subtitling is not really a valid option when it comes to enjoying the audiovisual content. They claim they do not understand the English audio, find the original voices odd and are not used to subtitles, so they say they cannot read them (Orrego-Carmona 2014). Additionally, those who use subtitles do not necessarily consider them as their first option.…”
Section: The Reception Conditionsmentioning
confidence: 99%
“…According to Casarini (2014), viewership 2.0 tends to follow high-quality shows, consciously decide which shows are worth their time and make "an active effort to follow them with the shortest possible delay after their original broadcast" (2014, p. 60). We know that the preference for subtitling over dubbing in many traditionally dubbing countries is related to the audience's belief that subtitling gives them the opportunity to have a viewing experience which resembles that of the target audience of the original product (Casarini, 2014;Orrego-Carmona, 2014). For this audience, using interlingual subtitles does not seem to be the best option.…”
Section: The Predominance Of Intralingual Subtitlesmentioning
confidence: 99%
“…Users themselves recognize the value of different translation modes. A claim that surfaces often is the idea that using subtitles allows viewers to have an experience which is closer to the original (Casarini 2014b;Orrego-Carmona 2014). This reconfigures how viewers engage with content and might provide insights into the future of translation.…”
Section: Exploring the New Audiences Through Translation And Understamentioning
confidence: 99%